Effect of crude oil impacted sand on the properties of concrete. (2012)
This study investigates the effect of Crude Oil Impacted Sand (COIS) on some engineering properties of fresh and hardened concrete. Total Petroleum Hydrocarbon (TPH) test was carried out on samples from the study area to determine the level of crude oil contamination. Based on the test results, six levels (2.5%, 5%, 10%, 15%, 20% and 25%) of artificial contaminated sand were prepared and engineering properties including slump, compacting-factor, flow-table, compressive-strength, flexural-strength, water-absorption, linear-shrinkage, surface-resistivity, and fire resistance were determined using standard methods. Predictive models were developed and concrete mixes were designed using COIS for reinforced concrete stuctures. TPH of the soil samples varied from 8.6 to 14.1%. The slump, compacting factor, flow-table, and surface-resistivity of the COIS concrete increased with levels of contamination. Compressive-strength, flexural-strength, shrinkage, water absorption and fire-resistance of the COIS concrete reduced with increased level of contamination. Coefficient of determination, R2, of the models ranged from 0.823 to 0.998. Mix ratio of 1: 1.6 : 2.4 of cement : COIS: coarse aggregate was found to be appropriate at 0.45 w/c. The Crude Oil Impacted Sand concrete with not more than 10% contamination is suitable for use in low strength structures